Research on environmental regulation, environmental protection tax, and earnings management - Fu, Shiwen; Yuan, Jianguo; Xiao, Deyun; Chen, Zhiqiang; Yang, Gaorong (Frontiers in Environmental Science, 2023)
After the Chinese government put forward carbon peaking and carbon neutrality goals, the intensity of environmental regulation has reached an unprecedented height. Using a sample of heavily polluted A-share listed companies in Shanghai and Shenzhen from 2012 to 2018, we discuss the influence mechanism of environmental regulation and environmental tax on corporate earnings management in this study. We use multiple regression models to empirically verify the impact of environmental regulation, environmental tax, and their combined effect on corporate earnings management. We find that environmental regulations promote enterprises’ upward real earnings management and inhibit enterprises’ upward accrual earnings management. However, environmental taxes discourage firms from upward accrual earnings management. Moreover, environmental regulations and environmental tax jointly promote enterprises’ upward accrual earnings management and real earnings management. And there is heterogeneity among different enterprise natures, different enterprise sizes, enterprises in regions with different degrees of marketization, different intensities of government investment in environmental protection, and whether enterprises disclose their environmental protection concepts. The contribution of this paper is to put environmental regulation, environmental protection tax, and earnings management in the same analytical framework. We aim to combine the government’s macro policy with the enterprise’s micro behavior and to deeply analyze the impact and mechanism of environmental regulation, environmental protection tax, and their combined effect on enterprise earnings management. By analyzing the heterogeneity of these impacts from multiple dimensions, this study tries to expand the research horizon, fill the research gap, and provide theoretical support for the government to formulate comprehensive environmental regulation policies.